Deceased donor liver utilisation and assessment: consensus guidelines from the European Liver and Intestine Transplant Association - Hessheimer, Amelia; Hartog, Hermien; Marcon, Francesca; Schlegel, Andrea; Adam, René; Alwayn, Ian; Angelico, Roberta; Antoine, Corinne; Berlakovich, Gabriela; Bruggenwirth, Isabel; Calatayud, David; Cardini, Benno; et al. (Journal of hepatology, 2025)
Over the past two decades, the application of machine perfusion (MP) in human liver transplantation has moved from the realm of clinical exploration to routine clinical practice. Both in situ and ex situ perfusion strategies are feasible, safe, and may offer improvements in relevant post-transplant outcomes. An important utility of these strategies is the ability to transplant grafts traditionally considered too risky to transplant using conventional cold storage alone. While dynamic assessment and ultimately transplantation of such livers is an important goal for the international liver transplant community, its clinical application is inconsistent. To this end, ELITA (the European Liver and Intestine Transplant Association) gathered a panel of experts to create consensus guidelines regarding selection, approach, and criteria for deceased donor liver assessment in the MP era. An eight-member steering committee (SC) convened a panel of 44 professionals working in 14 countries in Europe and North America. The SC identified topics related to liver utilisation and assessment for transplantation. For each topic, subtopics were created to answer specific clinical questions. A systematic literature review was performed, and the panel graded relevant evidence. The SC drafted initial statements addressing each clinical question. Statements were presented at the in-person Consensus Meeting on Liver Discard and Viability Assessment during the ELITA Summit held from April 19-20, 2024, in Madrid, Spain. Online voting was held to approve statements according to a modified Delphi method; statements reaching ≥85% agreement were approved. Statements addressing liver utilisation, the definition of high-risk livers, and strategies and criteria for dynamic liver assessment are presented.